Praktek Kewirausahaan Mandiri Mahasiswa Institut Teknologi dan Kesehtan Aspirasi sebagai Upaya Peningkatan Skill Menuju Kemandirian Ekonomi - Amrullah, Lalu; Gaffar, Affan; Warsani, Ziana; Safitri Rahman, Rahayu; Malita, Soufa; Abdul Majid, Muhip (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
The aim of this service is to develop the entrepreneurial abilities of students at the Aspiration Institute of Technology and Health. Entrepreneurship service activities are carried out with three series of activities, namely preparation, implementation and evaluation activities. After carrying out this service activity, there was an increase in students' understanding of entrepreneurship. The measurement results show that 31% of students really understand, 63% understand and 6% don't understand. These results indicate that student entrepreneurship service activities provide benefits in increasing student understanding